2022
DOI: 10.1093/cvr/cvac049
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interplay between cardiomyocytes and non-myocytes in diabetic cardiomyopathy

Abstract: Patients with Type 2 diabetes mellitus (T2DM) frequently exhibit a distinctive cardiac phenotype known as diabetic cardiomyopathy. Cardiac complications associated with T2DM include cardiac inflammation, hypertrophy, fibrosis and diastolic dysfunction in the early stages of the disease, which can progress to systolic dysfunction and heart failure. Effective therapeutic options for diabetic cardiomyopathy are limited and often have conflicting results. The lack of effective treatments for diabetic cardiomyopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 379 publications
(406 reference statements)
0
11
0
Order By: Relevance
“…Nonmyocytes such as myofibroblasts may contribute to arrhythmogenesis by direct electrotonic modulation of conduction besides shortened APDs. Overall, our current experimental data together with an excellent supporting discussion by Phang and co‐workers 67 can present valuable information on how cellular interplay between cardiomyocytes (with a short AP) and nonmyocytes. By using both electrophysiological data performed either in vivo (ECGs) or in vitro (APs and ionic currents) and immunohistochemical data obtained in the heart tissue under an early‐stage MetS, we provided some novel data to demonstrate the possible important roles of cardiac nonmyocyte populations in the regulation of both electrical and biomechanical signaling in the heart through developing an extensive network of intercellular communication to maintain a proper balance among excitable cells, Cx43, and nonmyocytes (Figure 7A).…”
Section: Discussionmentioning
confidence: 53%
“…Nonmyocytes such as myofibroblasts may contribute to arrhythmogenesis by direct electrotonic modulation of conduction besides shortened APDs. Overall, our current experimental data together with an excellent supporting discussion by Phang and co‐workers 67 can present valuable information on how cellular interplay between cardiomyocytes (with a short AP) and nonmyocytes. By using both electrophysiological data performed either in vivo (ECGs) or in vitro (APs and ionic currents) and immunohistochemical data obtained in the heart tissue under an early‐stage MetS, we provided some novel data to demonstrate the possible important roles of cardiac nonmyocyte populations in the regulation of both electrical and biomechanical signaling in the heart through developing an extensive network of intercellular communication to maintain a proper balance among excitable cells, Cx43, and nonmyocytes (Figure 7A).…”
Section: Discussionmentioning
confidence: 53%
“…A central pathogenic mechanism of DHD is the inflammatory response, which exacerbates oxidative stress and endoplasmic reticulum stress [ 9 ]. Macrophages, which execute the inflammatory response, influence the course of DHD through the secretion of various inflammatory factors [ 10 ]. Therefore, a drug therapy targeting macrophages may be a promising new direction for improved DHD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac non-myocytes, typically endothelial cells, resident mesenchymal cells and leukocytes are critical for maintaining homeostasis of the heart ( 43 ). However, an increased ratio of cardiac non-myocytes to myocytes has been associated with diastolic dysfunction and pathologic cardiac hypertrophy ( 44 , 45 ). Specifically, established mediators of cardiac hypertrophy such as atrial natriuretic peptide, brain natriuretic peptide and angiotensin-II have shown to increase the ratio of non-myocyte to myocytes ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%